Clinical study of early rehabilitation training combined with negative pressure wound therapy for the treatment of deep partial-thickness hand burns - Liu, Canbin; Xie, Hongteng; Wei, Pei; Gong, Teng; Wu, Guohua; Xu, Zhaorong; Chen, Shun (Frontiers in Surgery, 2023)
Objective This study aims to explore the clinical effect of early rehabilitation training combined with negative pressure wound therapy (NPWT) for treating deep partial-thickness hand burns. Methods Twenty patients with deep partial-thickness hand burns were randomly divided into an experimental group (n = 10) and a control group (n = 10). In the experimental group, early rehabilitation training combined with NPWT was performed, including the proper sealing of the negative pressure device, intraoperative plastic brace, early postoperative exercise therapy during negative pressure treatment, and intraoperative and postoperative body positioning. Routine NPWT was conducted in the control group. Both groups received 4 weeks of rehabilitation after wounds healed by NPWT with or without skin grafts. Hand function was evaluated after wound healing and 4 weeks after rehabilitation, including hand joint total active motion (TAM) and the brief Michigan Hand Questionnaire (bMHQ). Results Twenty patients were involved in this study, including 16 men and 4 women, aged 18–70 years, and the hand burn area ranged from 0.5% to 2% of the total body surface area (TBSA). There was no significant difference in TAM and bMHQ scores between the two groups after negative pressure removal. After 4 weeks of rehabilitation training, the TAM scores and bMHQ scores were significantly improved in both groups (p < 0.05); among them, those of the experimental group were both significantly better than those of the control group (p < 0.05). Conclusion The application of early rehabilitation training combined with NPWT to treat deep partial-thickness hand burns can effectively improve hand function.